Animal Reproduction in Veterinary Medicine 2021
DOI: 10.5772/intechopen.90774
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sow Sexual Behavior and the Application of the Boar Pheromone to Stimulate Sow Reproduction

Abstract: In this chapter, we review the sexual behavior of domestic pigs, and the visible or measurable anatomical features of the pig that will contribute to detecting sows in estrus. We also summarize olfactory organs, and the effects of a sexual pheromone on pig's biology and sow reproductive performance. We discuss the role of a live boar in the heat detection where the female is in breeding crates. However, there is an increasing interest in being able to breed sows without a boar present. Farm workers must be tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Pheromones play major role in reproduction in mammals (13,7,9), however, a few studies have demonstrated the pheromone synthesis molecular pathways and their specified role in reproduction. In this study, two putative sex pheromones (androstenone and androstenol) which we identified in mouse deer showed that mouse deer P450C17 gene possess an andien-β-synthase activity to transform pregnenolone to 5,16-androstadien-3β-ol, Although he 5,16-androstadien-3β-ol is considered to be an intermediate and precursor in the 16 androstene pathway leading to the biosynthesis of androstenone and androstenol (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pheromones play major role in reproduction in mammals (13,7,9), however, a few studies have demonstrated the pheromone synthesis molecular pathways and their specified role in reproduction. In this study, two putative sex pheromones (androstenone and androstenol) which we identified in mouse deer showed that mouse deer P450C17 gene possess an andien-β-synthase activity to transform pregnenolone to 5,16-androstadien-3β-ol, Although he 5,16-androstadien-3β-ol is considered to be an intermediate and precursor in the 16 androstene pathway leading to the biosynthesis of androstenone and androstenol (34).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the pheromone plays various important roles in distantly related species such as in social interactions and organization (2), sexual attraction (3), communication between mother and offspring (4), dominance and aggregation behaviour (5), scent marking and territorial behaviour (6). Pheromones are known to influence the secretion of gonadotropin hormones, testosterone, and luteinizing hormones in mice (7), Sea lampreys (8), and sows (9). A significant relationship between pheromones and reproductive hormones in pigs (10) and Asian elephants (11) was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is a paucity of data on the length of time considered adequate for the SOA to diffuse. Despite the pig having a highly developed sense of smell, we know relatively little about the pig’s olfactory system and how pheromones affect their behaviour [ 26 , 27 ]. Ideally, more research is required to understand the role of olfactory organs in the pig and how different pheromone delivery mechanisms and length of exposure can influence the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory organs were reviewed by others in recent years and so here we provide a simplified overview. See other reviews that go into more detail on olfactory organs ( 13 , 14 ).…”
Section: Organs That Sense Semiochemicalsmentioning
confidence: 99%
“…The domestic pig has an extensive MOE and a functional Trigeminal sensory neurons and a VNO, but the GG and SO have not been found in the domestic pig ( 14 ). The pig VNO has only V1R receptors, but it does not have V2R or FPR receptors ( 18 , 24 ).…”
Section: Semiochemicals In Domestic Pigsmentioning
confidence: 99%